Enterococci vs non-lactic acid microflora as hygiene indicators for sweetened yoghurt - Birollo, G. A. (2001)
Coliforms are usually used as a measure of hygiene status in the processing and packaging of dairy products. However, their limited chances of survival have placed a question mark over this role in acid products. Some authors propose Enterococcus as a group for hygienic condition inspections in process lines of fermented dairy products. The aims of this work were, first, to evaluate the viability of enterococcus and non-lactic acid microflora (coliforms, Pseudomonas, Staphylococcus aureus and yeasts) in whole set sweetened yoghurt during refrigerated storage and Second, to evaluate the occurrence of bacterial contaminants in industrial process lines of whole set sweetened yoghurt through a critical control points plan (CCP). Test strains were inoculated at a level of 5.5 log orders. Enterococcus remained viable for 21 days and was still detectable after up to 49 days of cold storage. The viability of Pseudomonas was very poor (D-values lower than 0.69 days). Klebsiella spp., Escherichia coli and Citrobacter spp. showed D-values of 1.61, 1.85 and 2.56 days, respectively, while two S. aureus strains showed D-values of 0.61 and 1.56 days. Kluyveromyces marxianus var. lactis strains tested in this study remained viable for at least 42 days. The in vitro assays performed during this study demonstrated that enterococci could remain viable for a longer period than coliforms. However, from analysis of the industrial reality it became evident that in whole set yoghurt lines, coliforms are the most frequent contaminants. In addition, they can remain viable during the fermentation step and, in some cases, during cold storage of the product. Finally, coliform detection is cheaper and faster than enterococci counts. It can thus be concluded that enterococci have little value as hygiene indicators in the industrial processes of yoghurt. Consequently, coliforms are a suitable hygiene indicator as long as they are determined in the first days after manufacture.